2012
DOI: 10.1371/journal.pone.0047290
|View full text |Cite
|
Sign up to set email alerts
|

Apocrine-Eccrine Carcinomas: Molecular and Immunohistochemical Analyses

Abstract: Apocrine-eccrine carcinomas are rare and associated with poor prognosis. Currently there is no uniform treatment guideline. Chemotherapeutic drugs that selectively target cancer-promoting pathways may complement conventional therapeutic approaches. However, studies on genetic alterations and EGFR and Her2 status of apocrine-eccrine carcinomas are few in number. In addition, hormonal studies have not been comprehensive and performed only on certain subsets of apocrine-eccrine carcinomas. To investigate whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 58 publications
1
41
0
2
Order By: Relevance
“…Thus far, there is limited data regarding genetic changes associated with malignant progression in these tumors. Activating mutations in HRAS , PIK3CA , and possibly EGFR may serve as oncogenic drivers . Of these, HRAS mutations have also been reported in poromas .…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, there is limited data regarding genetic changes associated with malignant progression in these tumors. Activating mutations in HRAS , PIK3CA , and possibly EGFR may serve as oncogenic drivers . Of these, HRAS mutations have also been reported in poromas .…”
Section: Discussionmentioning
confidence: 99%
“…110 The TP53 mutation has been reported in 2 cases of spiradenocarcinomas 81 and one case of malignant cylindroma. 79 Chondroid Syringoma and Malignant Chondroid Syringoma.-Chondroid syringoma, also known as benign mixed tumor, is a rare tumor of the vulva, with only a few cases reported in the literature. [111][112][113][114][115] In the vulva, these lesions are thought to arise from underlying sweat glands or Bartholin glands.…”
Section: 100mentioning
confidence: 99%
“…Studies have shown a strong correlation of androgen receptor expression in cutaneous apocrine carcinoma, raising the potential for antiandrogen therapy. 79,118 Extramammary Paget Disease.-Extramammary Paget disease can be either primary or secondary. Primary EMPD can be either an intraepithelial neoplasm with or without an associated invasive component or a manifestation of an underlying primary adenocarcinoma.…”
Section: 100mentioning
confidence: 99%
See 2 more Smart Citations